2016
DOI: 10.1099/jmm.0.000371
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota dysbiosis: a new piece in the understanding of the carcinogenesis puzzle

Abstract: Cancer is defined as an uncontrolled proliferation of malignant cells in a host and it is one of the main causes of death worldwide. Genetic and environmental factors play an important role in its development, and the involvement of microbial communities has also recently been recognized. The close relationship that characterizes the colonization by human commensal communities involves health risks, particularly when the homeostasis is disturbed. It has been hypothesized that this process may lead to cancer by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 92 publications
1
77
0
2
Order By: Relevance
“…Over the last few decades, an increasing body of studies has indicated the assemblage of gut microbiota influences the formation and progression of CRC. [16][17][18][19] However, few studies focus on the difference of gut microbiome in paired tumor and adjacent normal tissues of CRC patients. In this study, we used 16S rRNA sequencing to show the profile of the gut microbiome in Chinese CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few decades, an increasing body of studies has indicated the assemblage of gut microbiota influences the formation and progression of CRC. [16][17][18][19] However, few studies focus on the difference of gut microbiome in paired tumor and adjacent normal tissues of CRC patients. In this study, we used 16S rRNA sequencing to show the profile of the gut microbiome in Chinese CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Such dysbiosis, or disturbance in microbial community membership, structure or function, can consist of a loss of specific beneficial bacteria or a critical loss of diversity among the beneficial bacteria. This produces a state termed a pathobiome, defined as loss of the health‐promoting microbiome with a predominance of disease‐producing pathogens.…”
Section: Microbiome and Tumorigenesismentioning
confidence: 99%
“…Lately, the effects of HFD on gut microbiota dysbiosis are widely concerned . Dysbiosis is defined as a disturbance in the microbiome structure, such as loss of beneficial microorganisms, and expansion of pathological microorganisms, promoting the development of CRC . However, the specific mechanisms that how HFD‐induced dysbiosis affects intestinal carcinogenesis remain to be clarified.…”
Section: Introductionmentioning
confidence: 99%